Laparoscopic Management of Interstitial Pregnancy and Fertility Outcomes after Ipsilateral Salpingectomy – Three Case Reports - Manea, Cristina; Pavlidou, Evangelia; Urias, Aline Andrey; Bouquet de la Jolinière, Jean; Dubuisson, Jean Bernard; Feki, Anis (Frontiers in Surgery, 2014)
Background. Interstitial pregnancy after ipsilateral salpingectomy is a rare event with potentially serious consequences. Optimal management strategy remains uncertain and debated. In addition, fertility sparing is determinant of the treatment choice. Cases. Here we report three cases of interstitial pregnancy occurring after homolateral salpingectomy. We expose the therapeutic option held in all three situations, which associated laparoscopic procedure followed by intramuscular methotrexate injection, with successful outcome for all patients. We also report the fertility outcome for the first patient, discussing the timing and mode of delivery. Cesarean section at term was performed for this patient. Conclusion. In these three situations we obtained a successful result using a minimally invasive surgical approach combined with systemic methotrexate injection. Cesarean section at term for subsequent intrauterine pregnancy seems to be the safest delivery strategy, although no clear data exist in literature.